Pengaruh Pemanfaatan Sistem Informasi Pemerintahan Daerah (SIPD) dan Kompetensi SDM terhadap Kualitas Laporan Keuangan melalui Sistem Pengendalian Internal Pemerintahan (SPIP) - Nur Rizqikah; Chairul Adhim; Syafrudin Syafrudin (ProBisnis : Jurnal Manajemen, 2026)
This study aimed to investigate the effect of the Regional Government Information System and human resource competence on the quality of local government financial reports, mediated by the Government Internal Control System. The research addressed the persistent challenges and fluctuating audit opinions regarding financial report quality in Dompu Regency despite existing technological interventions. A quantitative explanatory survey approach was employed, utilizing a saturated sample of fifty civil servants directly involved in financial management at the Regional Financial and Asset Management Agency of Dompu Regency. Data analysis was performed using Partial Least Squares Structural Equation Modeling. The results showed that the utilization of the regional information system had a positive and significant direct effect on both the quality of financial reports and the internal control system. Human resource competence positively influenced internal control but lacked a significant direct impact on financial report quality. Furthermore, the internal control system significantly improved financial report quality and partially mediated the effect of the information system. The study concluded that optimizing information technology required an effective internal control mechanism to truly transform technical utilization into optimal financial accountability.